2022
DOI: 10.3389/fpls.2022.1062722
|View full text |Cite
|
Sign up to set email alerts
|

HD2A and HD2C co-regulate drought stress response by modulating stomatal closure and root growth in Arabidopsis

Abstract: Histone deacetylase 2 (HD2) is a unique family of histone deacetylases (HDACs) in plants. Despite evidence that certain HD2 family HDACs play an important role in plant growth and stress response, the coordination of HD2s in these processes remains largely unknown. We found that HD2-type, HD2A and HD2C coordinate to play a role in drought stress response in Arabidopsis. We showed that the hd2a.hd2c double mutant (Mac16) exhibit decreased drought survival and increased water loss as compared to the single mutan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…The survey revealed that, in the stable QTL 1, B. napus gene BnaA07p10740 ( At1g29290 , C‐TERMINALLY ENCODED PEPTIDE 14 , CEP14 ) contributes to root biomass production (Huang et al, 2023b); BnaA07p10110 ( At1g29950 , SUPPRESSOR OF ACAULIS LIKE 3 , SACL3 ) to root meristem size and root growth (Katayama et al, 2015); BnaA07p10090 ( At1g30040 , GIBBERELLIN 2‐OXIDASE 2 , GA2OX2 ) to gibberellic acid homeostasis for maintaining root growth (Tahir et al, 2022); and BnaA07p10020 ( At1g30270, CBL‐INTERACTING PROTEIN KINASE 23, CIPK23 ) to environmental stress response, including nitrate imbalance (Ródenas & Vert, 2021). In the stable QTL 2, C07p00330 ( At2g20610 , SUPERROOT 1 , SUR1 ) regulates auxin biosynthesis and lateral root patterning (Boerjan et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The survey revealed that, in the stable QTL 1, B. napus gene BnaA07p10740 ( At1g29290 , C‐TERMINALLY ENCODED PEPTIDE 14 , CEP14 ) contributes to root biomass production (Huang et al, 2023b); BnaA07p10110 ( At1g29950 , SUPPRESSOR OF ACAULIS LIKE 3 , SACL3 ) to root meristem size and root growth (Katayama et al, 2015); BnaA07p10090 ( At1g30040 , GIBBERELLIN 2‐OXIDASE 2 , GA2OX2 ) to gibberellic acid homeostasis for maintaining root growth (Tahir et al, 2022); and BnaA07p10020 ( At1g30270, CBL‐INTERACTING PROTEIN KINASE 23, CIPK23 ) to environmental stress response, including nitrate imbalance (Ródenas & Vert, 2021). In the stable QTL 2, C07p00330 ( At2g20610 , SUPERROOT 1 , SUR1 ) regulates auxin biosynthesis and lateral root patterning (Boerjan et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…In Arabidopsis, loss of HDA19 could enhance plant drought resistance [ 79 ], whereas the drought tolerance was reduced in hda9 mutants [ 36 ]. The Arabidopsis HD2A, HD2C, and HD2D were described as positive regulators of drought resistance since overexpression of these three genes played enhanced tolerance to drought stress when compared with WT plants [ 47 , 48 , 50 ]. While in another study, the silencing of HD2D represses enap1enap2myb44 drought-sensitive phenotype, indicating HD2D negatively regulates plant drought response [ 80 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our results, we propose a model for the regulatory function of HD2A and HD2B in coordinating drought stress response (Figure 10). Under drought conditions, the expression of HD2A and HD2B was enhanced [48] and functioned together to enhance the deacetylation of NCED9 and ABA-dependent/independent drought-responsive genes, thus repressing the endogenous ABA synthesis and drought responses. Additionally, drought stress increases the endogenous ABA content, which represses the expression of HD2A and HD2B, suggesting a negative feedback loop between ABA and HD2A/HD2B accumulation (Figure 9B).…”
Section: Hd2a and Hd2b Function In Drought Tolerance By Affecting Aba...mentioning
confidence: 99%
See 1 more Smart Citation
“…In Arabidopsis thaliana, a model plant, the HD2-type histone deacetylase HD2C has been found to negatively regulate drought tolerance. HD2C represses the expression of drought-responsive genes by deacetylating histones in their promoter regions, leading to reduced gene expression and impaired drought response in the plant [29]. Conversely, in Arabidopsis, certain genes positively regulate salt stress tolerance by enhancing the expression of salt-responsive genes.…”
Section: Acetylation and Deacetylationmentioning
confidence: 99%